THE ROLE OF MEGENT INSTITUTION IN CONFLICT RESOLUTION IN SILTIE SOCIETY - Ezedin Fedlu Nuri, (International Journal of Innovations in Engineering Research and Technology, 2023)
Conflict occurs over different sources in Siltie society. In order to aver bad consequences of conflicts the rural society relies on different customary institutions such as Melcho. Taking the informal mechanisms of conflict resolution as one of the most important tools that maintain peace and order in the rural society, this research has been under taken in Megent institution of Siltie society, with the objective of studying the role of the institution in resolving conflicts. A total of fifteen purposive interviews with community elders have been undertaken in three Wordas of Siltie zone. In addition three observations have been undertaken in the research area. In order to meet objectives of the study, qualitative method was used for data gathering and interpretation. The researcher gathered and studied the process and observed same and derived of the roles through interpretation. The results show that the Megent institution plays roles such as peace and harmony in the society.